A report of a giant parathyroid adenoma - Rodrigues, Ana Catarina M.; Muller, Catarina; Moreira, Carlos; Alves, Duarte Gil; Fernandes, Sara; Caires, António Girão; Fernandes, Jorge; Caldeira, Carmo (International Surgery Journal, 2023)
Giant parathyroid adenoma is a rare condition characterized by the presence of an abnormally large tumor in the parathyroid gland. A 62-year-old patient diagnosed with primary hyperparathyroidism and severe nephrolithiasis leading to nephrectomy. During workup for etiologic origin of hyperparathyroidism she was found to have a giant parathyroid adenoma with 7,8x3,6x4,3 cm estimated dimensions, located posteriorly to the trachea and extending to the thoracic inlet. She was then submitted to a Kocher cervicotomy and a partial superior sternotomy. The diagnosis is initially made throw laboratorial tests that reveal the elevated calcium and PTH levels. After diagnosis, imaging studies are essential to locate the gland in order to safely remove the entire associated adenoma. Management of giant adenoma is surgical with most patients achieving cure after the gland excision.